Affectivity in danish patients with emotional disorders: assessing the validity of the Positive and Negative Affect Schedule (PANAS) - Oliver Rumle Hovmand; Nina Reinholt; Anne Bryde Christensen; Anita Eskildsen; Bo Bach; Mikkel Arendt; Stig Poulsen; Morten Hvenegaard; Sidse M. Arnfred (BMC Psychiatry, 2023)
Abstract Background The Positive and Negative Affect Schedule (PANAS) was designed to measure trait positive affect (PA) and trait negative affect (NA). Methods The Danish PANAS was administered to outpatients with depression and anxiety disorders. Internal consistency was assessed using Cronbach’s alpha and McDonald’s omega and factorial structure was evaluated using confirmatory factor analysis (CFA). Convergent validity was evaluated by means of correlations with the negative affectivity and the detachment domain of the Personality Inventory for DSM-5 Short Form (PID-5-SF), the Hamilton Anxiety Rating Scale 6 (HARS-6) and the Hamilton Depression Rating Scale 6 (HDRS-6). Results PANAS Scores of 256 patients were analyzed. Cronbach’s alpha and McDonald’s omega showed good internal consistency for both the PA score (alpha = .84 and omega = .89) and the NA score (alpha = .86 and omega = .90). CFA analysis confirmed a structure with two factors corresponding to the PA and NA factors. PA was negatively correlated with the detachment domain of PID-5 (r = -.47), HARS-6 (r = -.15) and HDRS-6 (r = -.37). NA was positively correlated with PID-5-SF negative affectivity domain (r = .43), HARS-6 (r = .51) and HDRS-6 (r = .52). Discussion The Danish PANAS has promising internal consistency and construct validity, which are comparable to other studies of the instrument.